2018
DOI: 10.1002/agr.21590
|View full text |Cite
|
Sign up to set email alerts
|

Can members’ WeChat engagement affect relational outcomes in community‐supported agriculture? Empirical evidence from China

Abstract: Members' offline engagement is commonly believed to affect the producer-member relationship in communitysupported agriculture, however, little research focuses on engagement in the online context. Using qualitative data of 24 members and quantitative data of 279 members from China, this study uses a sequential exploratory mixedmethod design to explore the impact of members' WeChat engagement on relational outcomes. The findings indicate that WeChat engagement positively affects four relational outcomes: Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Thus, CSA community might be built on traditional, face-to-face interactions that take place on-farm, but also through shared interests and advocacy that can take place inperson or online. Research specific to social media and local food is less common, but one study found that among CSA members in China, engaging in social media with their farm was related to members feeling stronger social bonds and commitment to their farm (Tan and Chen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CSA community might be built on traditional, face-to-face interactions that take place on-farm, but also through shared interests and advocacy that can take place inperson or online. Research specific to social media and local food is less common, but one study found that among CSA members in China, engaging in social media with their farm was related to members feeling stronger social bonds and commitment to their farm (Tan and Chen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research in Norway shows that members who are more actively involved in farm activities have a higher evaluation of the farm, and their overall motivation for re-participating in the farm is higher [ 102 ]. In China, members’ online participation has a positive impact on social interaction, which also positively affects the satisfaction of CSA services [ 29 ]. Some researchers believe that if interaction is not emphasized and CSA members are only regarded as customers who buy products, the foundation of CSA may be damaged [ 5 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on membership retention has focused on surveys of CSA member satisfaction [19][20][21][22]. Prior research has examined factors such as price, convenience, trust, local food, product quality, customization, and online engagement that have been shown to positively influence membership joining and maintaining loyalty [3,21,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in developed and developing countries, have widely acknowledged the usefulness of such internet-based advisory sources. For instance, Tan et al [61] argue that in China, farmers access information about the marketing of farm produces using social media platforms such as WeChat, and in Australia, farmers also have a higher usage rate of website browsing [62]. Similarly, in the United Kingdom use of Twitter enables researchers and advisers to interact and share knowledge with farmers [63].…”
Section: Farmers' Use Of Ictbaismentioning
confidence: 99%